Observations of the brightest UHE Gamma-Ray Sources With the LHAASO-KM2A - Wu S. (2023)
Cosmic rays are high-energy charged particles that come from outer space. They play an important role in the evolution of our Galaxy. Gamma-ray emission produced by cosmic rays is a direct probe of cosmic rays and their accelerators. As a key sub-array of the Large High Altitude Air Shower Observatory (LHAASO), KM2A is the most sensitive gamma-ray detector at ultra-high energy (UHE, >100 TeV) band. Here, we report four of the brightest UHE sources measured by LHAASO, LHAASO J1825-1326, LHAASO J1908+0621, LHAASO J2108+5157 and LHAASO J2226+6057. The morphology and spectral energy distribution of these sources are studied respectively using the KM2A data collected from December 2019 to December 2020. The origin of the UHE gamma-ray emission is also discussed taking into account the implications from multi-wavelength observations.